Determination of the effective anticandidal concentration of denture cleanser tablets on some denture base resins - Yeliz Hayran; Işıl Sarikaya; Ali Aydin; Yadel Hazır Tekin (University of São Paulo, 2018)
Abstract Objective Although the effectiveness of chemical cleansing against Candida albicans biofilm has been shown, the effective concentration of denture cleanser tablets has not been studied. The aim of this study was to assess the effect of three denture materials against Candida albicans biofilm and to determine effective concentrations of denture cleanser tablets. Material and methods The surface-roughness of Acron-hi™, QC-20™ and Deflex™ (n=45 per resin) resins was standardized by using a profilometer and their contact angle or surface free energy was calculated. C. albicans biofilm was formed on all three resins and were treated with Polident 3 min™, Corega™ and Fittydent™ cleanser solutions at various concentrations and both resin-biofilm and cleanser-biofilm interest were determined by using a MTT protocol according to the European Committee on Antimicrobial Susceptibility Testing's antifungal susceptibility testing (AFST-EUCAST). Scanning electron microscopy was used to compare the efficacy of different resin materials against C. albicans biofilm. Anticandidal activity and surface free energy statistical parameters were calculated by using 3-way and 1-way ANOVA, respectively (p<0.05). Results Polident 3 min™ and Corega™ tablets significantly inhibited (p<0.05) the proliferation of C. albicans against all denture resins at 27-37 mg/mL. Scanning electron microscopy results indicated that there was no significant difference among resin specimens regarding biofilm formation on dentures. We failed to find a significant relationship between surface free energy and the anticandidal effect of resin types. However, the polarity value of the resins was statistically associated with their anticandidal activity. Conclusions The polarity of the resins, the concentrations of tablets and the chemical content of the cleanser may directly affect C. albicans biofilm formations. Polident 3 min™ and Corega™ tablets should be suggested for patients who use any denture resin types, whereas the Fittydent™ tablet should only be proposed for those who use Deflex™, when two tablets are dropped into 150 mL water.